Pemodelan Sistem Keamanan Snort Intrusion Detection System (IDS) Pada Jaringan Yang Berbasis Software Defined Network (SDN) - Yosef Asido Manalu; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Software Defined Network (SDN) is a centralized network where control plane and data plane embedded in different systems. However, controller is an indivual threat to the security of data packet that passes OpenFlow Network. Security on a computer network is the top priority in designing a network. This research is performed by designing a tree network topology in SDN from and simulated on the mininet software. Then, snort activation is done on protected Host with snort detection system. Attack test is done on Host 8 as an Attacker and Host 1 becomes the Target of attack using hping3 application. Test results of Ddos attack by Host 8 uses IP Address 192.168.10.14 and Host 1 uses IP Address 192.168.10.7. Attack priority level is done on Level 1 (high attack category). After detection by snort, notification is displayed on BASE with intrusion that processed by IDS with UDP messagesKeywords : SDN, Ddos, Security Network, Snort